Turi-Turian Ultop Si Jonaha Etnik Batak Toba: Kajian Sosiologi Sastra - Simamora, Eveline Mangerbang; Sinulingga, Jekmen; Sinaga, Warisman; Herlina, Herlina; Purba, Asriaty R (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Penelitian ini berjudul